The influence of customer personalization on customer satisfaction, engagement, and loyalty Indonesian E-commerce in the digital age - Maduwinarti, Ayun; Kusbianto, Nugraha; Mahendra, I.G.N. Andhika (International Journal of Innovative Research and Scientific Studies, 2025)
In the rapidly evolving landscape of Indonesian e-commerce, this research explores the intricate dynamics between customer personalization and its impact on customer loyalty. Positioned within a burgeoning market projected to exceed USD 95 billion by 2025, the study addresses the competitive challenges faced by e-commerce enterprises in retaining customers. Leveraging personalized content and interactions, the research delves into the mediating roles of customer engagement and customer satisfaction in shaping customer loyalty. Employing a quantitative approach, the research collected data through an online survey from individuals who made multiple purchases on Indonesian e-commerce platforms. The study’s structural equation modeling analysis confirmed the hypotheses, indicating a significant positive influence of customer personalization on customer engagement and satisfaction, which, in turn, positively and significantly affects customer loyalty. The findings underscore the strategic importance of customer personalization in enhancing customer engagement and satisfaction and ultimately fostering customer loyalty in the Indonesian e-commerce context. The research contributes valuable insights for businesses aiming to utilize personalization initiatives. The recommendations emphasize the need for e-commerce brands to prioritize customer personalization strategies in their marketing efforts, providing personalized content and tailored initiatives to strengthen customer loyalty. Future research is encouraged to explore additional variables, such as customer trust, to further illuminate the determinants of customer loyalty in the context of Indonesian e-commerce.